Interleukin-27 prevents LPS-induced inflammatory osteolysis by inhibiting osteoclast formation and function - Li, Xianghe (Am J Transl Res, 2019)
Osteolysis is a serious complication of several chronic inflammatory diseases and is closely associated with a local chronic inflammatory reaction with a variety of causes. Inflammatory factors and osteoclastogenesis can enhance bone erosion. Interleukin-27 (IL-27) is speculated to play an important role in the physiological immune response. However, there are few studies on its effects on osteoclastogenesis. In this study, IL-27 was shown to inhibit receptor activator nuclear factor-κB ligand (RANKL)-induced osteoclastogenesis. The gene expression levels of osteoclast (OC)-specific genes, such as nuclear factor of activated T-cells cytoplasmic 1 (NFATc1) and C-FOS, which are essential for OC differentiation and bone resorption, were significantly reduced. Further investigating the underlying mechanism, we found that IL-27 significantly reduced RANKL-induced osteoclastogenesis by inhibiting the phosphorylation of IκB and phosphorylation of nuclear factor κB (NF-κB) p65. Furthermore, IL-27 was shown to inhibit lipopolysaccharide (LPS)-induced osteolysis in vivo. Collectively, these results indicate that IL-27 may be a potential candidate for the treatment of osteolytic diseases.